Channel Modeling Using Rayleigh and Rice Sum Approximation - Orellana-Prato, R (Institute of Electrical and Electronics Engineers Inc., 2024)
In this paper we develop an identification technique for the multipath wireless channel utilizing a discrete sum distribution approximation. We focus on three of the main distributions for the multi-path channel: Rayleigh, Rice and Nakagami-m. The distributions are approximated using a weighted sum of a Rayleigh and up to three distributions. The estimation procedure is based on the Maximum Likelihood approach and Akaike s Information Criterion. We show via simulations that when the channel is Rayleigh distributed, the estimation yields the correct Rayleigh distribution. When the channel distribution is Rice, the estimation yields one Rician term, whilst when the true channel distribution is Nakagami- m, the estimation yields an adequate approximation with a Rayleigh and Rice terms. © 2024 IEEE.